2014
DOI: 10.1016/j.jaci.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Twin and family studies reveal strong environmental and weaker genetic cues explaining heritability of eosinophilic esophagitis

Abstract: Background Eosinophilic esophagitis (EoE) is a chronic antigen-driven allergic inflammatory disease, likely involving the interplay of genetic and environmental factors, yet their respective contributions to heritability are unknown. Objective To quantify risk associated with genes and environment on familial clustering of EoE. Methods Family history was obtained from a hospital-based cohort of 914 EoE probands, (n=2192 first-degree “Nuclear-Family” relatives) and the new international registry of monozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
196
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 236 publications
(207 citation statements)
references
References 74 publications
1
196
0
10
Order By: Relevance
“…47 In contrast, familial multisystem HES appears to be extremely rare. Autosomal dominant transmission of HE has been mapped to chromosome 5q31-33 in one extended family.…”
Section: Familial He/hesmentioning
confidence: 99%
“…47 In contrast, familial multisystem HES appears to be extremely rare. Autosomal dominant transmission of HE has been mapped to chromosome 5q31-33 in one extended family.…”
Section: Familial He/hesmentioning
confidence: 99%
“…IL-13 is thought to mediate these responses through epigenetic changes, including elevated levels of histone acetylation and decreased DNA methylation in the promoters of critical mediators, such as eotaxin 3 (also known as CCL26), CAPN14, and NTRK1 (14)(15)(16). Co-occurrence of epigenetic changes with transcriptional response suggests that integrating transcriptional and epigenetic analyses may serve as a useful approach to discover molecules with functional roles in EoE pathogenesis, especially since EoE is influenced by gene-environment interactions (17).…”
Section: Introductionmentioning
confidence: 99%
“…This latter low incidence suggests a strong environmental contribution to acquiring this disease. This conclusion is supported by the finding that although the nuclear-family heritability appeared to be high (72.0%), the twins cohort analysis revealed that this high levels are likely due to a powerful role of a common environment that occurs in 81.0% of the cases [45] .…”
Section: Pathological Abnormalitiesmentioning
confidence: 73%